2019
DOI: 10.17776/csj.535751
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Some Qualities Parameters and Use of Strip Loin Beef (M. Longissimus dorsi) Powder in Bread Enrichment

Abstract: In this study, the protein content of the bread, that is also known as rich in carbohydrate content, is enriched by using strip loin beef (M. longissimus dorsi) powder as the additive. In order to meet the daily protein needs of individuals, bread was prepared with the addition of certain amounts (3%, 5%, 7%, and 10%) of beef minced powder to the wheat flour. The protein content of the bread samples with the addition of strip loin beef (M. longissimus dorsi) powder were increased from 14.41%, 16.03%, 17.43% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In this study, chicken meat powder-breads expressed significantly higher protein content relative to the control breads, diluting the significant effect of hydrophobicity of >35% amino acids in wheat gluten [ 54 ] hence accounting for the disparity in moisture contents. Similar observation was made in other studies involving wheat bread enrichment with spent hen meat powder [ 55 ], chicken meat powder [ 38 ], cheese [ 56 ], grasshopper powder [ 31 ] and strip loin beef powder [ 33 ]. In contrast, Monteiro et al [ 57 ] reported decrease in moisture content with increasing level of tilapia waste flour in wheat bread, possibly due to the dominating hydrophobic components of the formulation mix.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, chicken meat powder-breads expressed significantly higher protein content relative to the control breads, diluting the significant effect of hydrophobicity of >35% amino acids in wheat gluten [ 54 ] hence accounting for the disparity in moisture contents. Similar observation was made in other studies involving wheat bread enrichment with spent hen meat powder [ 55 ], chicken meat powder [ 38 ], cheese [ 56 ], grasshopper powder [ 31 ] and strip loin beef powder [ 33 ]. In contrast, Monteiro et al [ 57 ] reported decrease in moisture content with increasing level of tilapia waste flour in wheat bread, possibly due to the dominating hydrophobic components of the formulation mix.…”
Section: Resultssupporting
confidence: 87%
“…Previously, wheat bread has been fortified/enriched with legumes [ 24 ], fruits and vegetables [ 25 ], herbs [ 26 ], roots and tubers [ 27 ], grains [ 28 ], insects [ [29] , [30] , [31] , [32] ], beef [ 33 ], fish [ [34] , [35] , [36] , [37] ], mushroom [ 6 ] and chicken meat [ 38 , 39 ] in attempts to revamp the nutritional status. These studies have reported appreciable levels of proteins and other key nutrients in the end products, critical for human nutritional improvement.…”
Section: Introductionmentioning
confidence: 99%